Investigating Students’ High-Order Thinking Skills in Storytelling at Elementary Level: A Case Study - Lidiporu, Givens Rindu Magnificat Ade; Sumarni, Sri (STAIRS: English Language Education Journal, 2022)
The purpose of this qualitative case study is to investigate Higher Order Thinking Skills (HOTS) in speaking activities, especially in storytelling for primary school children. Data collection methods included (1) interviews to investigate the extent of HOTS understanding, implementation, tactics, students' reactions, and the impact of storytelling activities, (2) observations, and (3) documentation. An English Club teacher and the students at the elementary level served as the research's data source. Data were validated using source and technique triangulation. The interactive analysis of the Miles and Huberman model was utilized for data analysis, comprising processes of data reduction, data presentation, and drawing conclusions. The results showed that the teacher grasped the HOTS feature and used it in narrative exercises. The strategies included asking questions, allowing youngsters to work on projects, and solving difficulties. Students’ reactions toward the storytelling activities varied because their focus levels are different. HOTS components in storytelling activities such as analyzing, evaluating, and creating have a significant impact on the ability to think critically, and creatively, communicate, work together, solve issues, and boost self-confidence. Due to these diverse abilities, HOTSs help children understand the storyline better and encourage them to take risks.